Pemanfaatan Energi Surya Sebagai Upaya Pengurangan Emisi di Wilayah Provinsi Riau - Sanya Gautami; Mubarak Mubarak; Yusni Ikhwan Siregar (Pelantar Press, 2023)
This research focus on assessing the spatial distribution area of solar energy potential in Pekanbaru using ECMWF ERA5 from 2012-2022 and analysing the environmental, social, and economic aspects based on solar energy utilisation. Using overlay and intersection techniques in ArcGIS, Pekanbaru's average solar energy potential is around 5,0-5,5 kWh/m2, and around 438.227-482.050 MWh/year of photovoltaic energy can be harvested from rooftop photovoltaic installation. Moreover, by utilising rooftop photovoltaic systems, the potential of CO2 emission can be reduced at around ±411.934-453.127 tonCO2/year, and it is predicted to reduce CO2 emission from households in 2022 by up to 52%. On the other hand, a questionnaire is used to describe the level of the community's understanding related to the beneficial effects of solar energy. Based on 100 respondents, it is found that around 58% of people don’t understand or are aware of rooftop photovoltaic, 20% of households think that the system is not necessary or urgently needed, and 22% of respondents argue that the high cost of installation is the primary consideration. The results reveal that the support from local governments is required for developing PV system as this system is one of the possible solutions to reduce greenhouse gases (GHGs).